Owner‐Management, Firm Age, and Productivity in Italian Family Firms. (April 2014) - Cucculelli, Marco; Mannarino, Lidia; Pupo, Valeria; Ricotta, Fernanda; Carsrud, Alan; Cucculelli, Marco
<x xml:space="preserve">Abstract</x> Using total factor productivity as a measure of corporate performance, we find that Italian family‐run firms are less productive than firms run by outside managers and the result is robust to potential endogeneity of management regime. This difference tends to vanish when the age of the firms is taken into account. Also, when considering family‐owned firms only, there is no difference in performance between outside managers and family managers.